2021
DOI: 10.1002/jclp.23159
|View full text |Cite
|
Sign up to set email alerts
|

Predicting suicidal ideation in a longitudinal high‐risk sample: Multilevel analyses and 12‐month trajectories

Abstract: Background: The Interpersonal Theory of Suicide states that suicidal ideation (SI) results from perceived burdensomeness (PB) and thwarted belongingness (TB). Crosssectional studies found associations with SI. This study examined the prospective prediction of SI.Methods: Three hundred and eight inpatients reporting severe SI or a recent suicide attempt were assessed four times within 12 months. The prediction of SI was examined using multilevel analyses, group comparisons, and logistic regression analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(81 reference statements)
1
3
0
1
Order By: Relevance
“…This study analysed data from a prospective multicentre study, longitudinally investigating predictors of suicidal ideation and behaviour over the course of 12 months. Further results from this study can be found elsewhere (Forkmann et al, 2020, b; furthermore: Brailovskaia et al, 2019; Höller et al, 2020, 2021; Lucht et al, 2020; Paashaus et al, 2019, 2020, 2021; Rath, Teismann, Hoeller, et al, 2021; Rath, Teismann, Schmitz, et al, 2021; Schönfelder et al, 2020, 2021; Teismann et al, 2021; Wannemueller et al, 2020). In the current examination, only data from the first assessment ( T 0 ) were analysed.…”
Section: Methodssupporting
confidence: 64%
“…This study analysed data from a prospective multicentre study, longitudinally investigating predictors of suicidal ideation and behaviour over the course of 12 months. Further results from this study can be found elsewhere (Forkmann et al, 2020, b; furthermore: Brailovskaia et al, 2019; Höller et al, 2020, 2021; Lucht et al, 2020; Paashaus et al, 2019, 2020, 2021; Rath, Teismann, Hoeller, et al, 2021; Rath, Teismann, Schmitz, et al, 2021; Schönfelder et al, 2020, 2021; Teismann et al, 2021; Wannemueller et al, 2020). In the current examination, only data from the first assessment ( T 0 ) were analysed.…”
Section: Methodssupporting
confidence: 64%
“…The third sample ( n = 3 08) consisted of acutely suicidal patients hospitalized at the time of the survey. Data of this sample was collected as part of the project PRESS ( Predictors of the Development of Suicidal Thoughts and Behavior in Longitudinal Section : An Evaluation of the Interpersonal Theory of Suicidal Behavior in High-Risk Patients ) at the University of Duisburg-Essen, the Ruhr University Bochum, and the University of Leipzig [e.g., 36 ]. Data was collected in 13 psychiatric wards of German hospitals from September 2016 to March 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Hagan et al, 2015;Talley et al, 2016;Wolford-Clevenger et al, 2019] als auch widersprechenden Befunden [z.B. Christensen et al, 2013;Baertschi et al, 2017;Forkmann et al, 2021;Rath et al, 2021].…”
Section: Interpersonale Theorie Suizidalen Verhaltensunclassified